DIGITAL MANAGEMENT - Islomjon Nurmukhammadov (Galaxy International Interdisciplinary Research Journal, 2024)
The article provides new requirements for modern management and examples of digital management. Digitalization and digital management offer new opportunities and challenges. The goal is to increase the efficiency of all enterprise processes, improve working conditions and quality. Digitalization and digital management are an integral part of development and progress